Computational Research in the Post-API Age. - Freelon, Deen (Political Communication)
The article discusses the significance of computational research in graduate education in what the author identifies as the post-Application Program Interface (API) era, particularly focusing on the concepts of Web scraping and terms of service (TOS). The article discusses social media outlets Facebook and Twitter.